Considering the Specific Impact of Harsh Conditions and Oil Weathering on Diversity, Adaptation, and Activity of Hydrocarbon-Degrading Bacteria in Strategies of Bioremediation of Harsh Oily-Polluted Soils. (24th January 2017) - Al Disi, Zulfa; Jaoua, Samir; Al-Thani, Dhabia; Al-Meer, Saeed; Zouari, Nabil
Abstract : Weathering processes change properties and composition of spilled oil, representing the main reason of failure of bioaugmentation strategies. Our purpose was to investigate the metabolic adaptation of hydrocarbon-degrading bacteria at harsh conditions to be considered to overcome the limitations of bioaugmentation strategies at harsh conditions. Polluted soils, exposed for prolonged periods to weathered oil in harsh soils and weather conditions, were used. Two types of enrichment cultures were employed using 5% and 10% oil or diesel as sole carbon sources with varying the mineral nitrogen sources and C/N ratios. The most effective isolates were obtained based on growth, tolerance to toxicity, and removal efficiency of diesel hydrocarbons. Activities of the newly isolated bacteria, in relation to the microenvironment from where they were isoalted and their interaction with the weathered oil, showed individual specific ability to adapt when exposed to such factors, to acquire metabolic potentialities. Among 39 isolates, ten identified ones by 16S rDNA genes similarities, including special two Pseudomonas isolates and one Citrobacter isolate, showed particularity of shifting hydrocarbon-degrading ability from short chain n -alkanes ( n -C12– n -C16) to longer chain n -alkanes ( n -C21– n -C25) and vice versa by alternating nitrogen source compositions and C/N ratios. This is shown for the first time.